Reología, comportamiento físico-mecánicos y de durabilidad de hormigones con nanosílice - Téllez Girón, E.; Martín Acosta, A .N.; Pérez Hernández, A.; Verdecia RodríguezU. (Revista ALCONPAT, 2012)
Nanosilice based in nanometric amorphous silica is one of the aplications of nanotechnology in the building industry, that has the same use than microsilica, but with the advantage that it does not produce environmental pollution or respiratory complains due to inhalation. We give the results of the physical characterization of two commercial nanosilice compounds by the admixtures characterization methods and electronic microscopy analysis to determine the fundamental compound, its pozzolanic activity in mortars, as well as its capillary absorption, ultrasonic pulse speed, volumetric mass, water penetration resistance coefficient, water absorption coefficient and effective porosity in concrete with nanosilice and in ordinary concrete with natural pozzolans and superplasticizer admixtures like comparative patterns. Results show a better behavior of durability in concretes with nanosilice. Keywords: nanotechnology; nanosilica; microsilica; chemical admixtures; additions.